Comparative transcriptome analysis of diurnal alterations of liver glycogen structure: A pilot study. (1st November 2022) - Liu, Qing-Hua; Wang, Zi-Yi; Tang, Jia-Wei; Mou, Jing-Yi; Ma, Zhang-Wen; Deng, Bin; Liu, Zhao; Wang, Liang
Abstract: Molecular mechanisms behind structural alterations between fragile and stable glycogen α particles in liver are not clear yet. In this pilot study, we re-examined the diurnal alterations of glycogen structure from the perspective of liver tissue transcriptome. By comparing the structures of liver glycogen from mice at 12 am, 8 am, 12 pm, and 8 pm (light-on: 6 am; light-off: 6 pm), we re-confirmed that the liver glycogen was fragile at 12 am and 8 am and stable at 12 pm and 8 pm as previously reported. The structural differences of glycogen particles at 12 am and 12 pm were thoroughly compared via transcriptomics. Differentially expressed genes (DEGs) with statistical significance were identified, while expression level of the gene ppp1r3g (log2 Fold_Change = −6.368, P -value = 2.89E−04) that encoded PPP1R3G with glycogen binding domain was most significantly changed, which provided preliminary clues to the structural alterations of glycogen α particles during the diurnal cycle. Graphical abstract: Unlabelled Image